Neuropsychological and Psychiatric Features of Children and Adolescents Affected With Mitochondrial Diseases: A Systematic Review - Riquin, Elise; Duverger, Philippe; Cariou, Cindy; Barth, Magalie; Prouteau, Clément; Van Bogaert, Patrick; Bonneau, Dominique; Roy, Arnaud (Frontiers in Psychiatry, 2020)
Mitochondrial diseases (MDs) are a group of clinically heterogeneous genetic disorders that arise as the result of dysfunctional mitochondria. Only few medical articles deal with neuropsychological or psychiatric aspects of MDs. Aim: The present article aims to provide a systematic review of neuropsychological and psychiatric aspects of MDs. Methods: In order to identify all studies dealing with psychiatric and neuropsychological aspects of MDs in children and adolescents, we performed a search in the medical literature between April 2009 and April 2019 using PubMed, Cochrane and Web of Science and we defined inclusion and exclusion criteria. Results: We found only seven studies that satisfy the inclusion requirements and criteria. The main psychiatric aspects reported in MDs were depressive and behavioral disorders. With regard to the neuropsychological aspects of MDs, developmental analyses showed an overall deterioration, learning difficulties, and developmental delay. Interpretation: Children and adolescents with MDs may present psychiatric symptoms and neuropsychological impairment. A more systematic investigation of psychiatric and neuropsychological features of MDs is needed to foster a better understanding of the phenotype of these diseases and their links with the genotype, which may have significant implications for the developmental trajectories of patients.